2011
DOI: 10.1162/jocn.2010.21465
|View full text |Cite
|
Sign up to set email alerts
|

Modality-dependent “What” and “Where” Preparatory Processes in Auditory and Visual Systems

Abstract: The present study examined the modality specificity and spatio-temporal dynamics of "what" and "where" preparatory processes in anticipation of auditory and visual targets using ERPs and a cue-target paradigm. Participants were presented with an auditory (Experiment 1) or a visual (Experiment 2) cue that signaled them to attend to the identity or location of an upcoming auditory or visual target. In both experiments, participants responded faster to the location compared to the identity conditions. Multivariat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 56 publications
1
5
0
Order By: Relevance
“…When the location is fixed and the sound identity is changed, only one stimulus repetition is needed to yield maximum P2 suppression, but when the location is changed, two more stimulus repetitions are needed (Figure 5B, D) (It also is worth noting that the P2 amplitude of the D S S L trial at the second position was comparable to that of the S S D L trial at the fourth position). This faster adaptive response to sound location is in line with the results of Diaconescu et al [72] who found faster evoked responses to the location compared to the identity condition in a cue-target paradigm. Consequently, one could infer that it would be more advantageous to maintain vigilance to constant sounds that are moving.…”
Section: Discussionsupporting
confidence: 91%
“…When the location is fixed and the sound identity is changed, only one stimulus repetition is needed to yield maximum P2 suppression, but when the location is changed, two more stimulus repetitions are needed (Figure 5B, D) (It also is worth noting that the P2 amplitude of the D S S L trial at the second position was comparable to that of the S S D L trial at the fourth position). This faster adaptive response to sound location is in line with the results of Diaconescu et al [72] who found faster evoked responses to the location compared to the identity condition in a cue-target paradigm. Consequently, one could infer that it would be more advantageous to maintain vigilance to constant sounds that are moving.…”
Section: Discussionsupporting
confidence: 91%
“…The IPL may also act as an interface in which sound locations are remapped onto the visual co-ordinate system to guide motor responses. This hypothesis has received some support from a recent study using neuroelectric recordings which showed that preparation for responding to the location of a visual or an auditory target engages a similar neural network (Diaconescu et al, 2010 ). However, further research is needed to understand when and where spatial information from various sources (e.g., auditory and visual) are combined together.…”
Section: Discussionmentioning
confidence: 99%
“…A recent EEG study [20] suggested that attentional control over auditory and visual “what” streams is predominantly modality specific. However, sound-object perception can certainly be affected by crossmodal information.…”
Section: Introductionmentioning
confidence: 99%